2020
DOI: 10.1101/2020.03.31.019349
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intergenerational pathogen-induced diapause inC. elegansis modulated bymir-243

Abstract: 15The interaction and communication between bacteria and their hosts modulate many 16 aspects of animal physiology and behavior. Dauer entry as a response to chronic exposure 17 to pathogenic bacteria in Caenorhabditis elegans is an example of a dramatic behavioral 18 decision to survive. This response depends on the RNAi machinery suggesting the 19 involvement of sRNAs as effectors. Interestingly, dauer formation occurs after two 20 87 we will first refer to mRNAs. Differential gene expression of animals f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…This implies that PMK-1–driven gene expression during exposure to OP50 PQE may be attributed to MET-2–mediated histone modification ( 51 ). The potential transgenerational impact of OP50 PQE on worms is further suggested by the enrichment of genes controlled by MIR-243, known for regulating intergenerational defense against pathogenic bacteria ( 52 ). A decrease in the levels of S -adenosylmethionine, a methylation donor, has been demonstrated to activate the pmk-1 pathway ( 53 ), possibly explaining that genes enriched by OP50 PQE are also regulated by genes controlling histone methylation ( met-2 , hpl-1 , and dpy-21 ).…”
Section: Discussionmentioning
confidence: 99%
“…This implies that PMK-1–driven gene expression during exposure to OP50 PQE may be attributed to MET-2–mediated histone modification ( 51 ). The potential transgenerational impact of OP50 PQE on worms is further suggested by the enrichment of genes controlled by MIR-243, known for regulating intergenerational defense against pathogenic bacteria ( 52 ). A decrease in the levels of S -adenosylmethionine, a methylation donor, has been demonstrated to activate the pmk-1 pathway ( 53 ), possibly explaining that genes enriched by OP50 PQE are also regulated by genes controlling histone methylation ( met-2 , hpl-1 , and dpy-21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Signals to induce F2 diapause were maternally transmitted for both pathogens and required the expression of dsRNA transporters ( sid‐1 , sid‐2 and sid‐3 ), RNAi processing genes ( rde‐1 , rde‐4 , sago‐1 , sago‐2 ) and the germline RNAi mediator alg‐2 . Subsequent transcriptomics revealed upregulation of the microRNA mir‐243‐3p in F2 progeny exposed to MST1 or PAO1 [74]. Experiments using PAO1 showed that the transcription factors DAF‐16, PQM‐1 and CRH‐2 are required for mir‐243 expression, and this enables dauer formation.…”
Section: Multigenerational Immunity In Response To Bacteriamentioning
confidence: 99%